Dystrybucja i rola sztyletów krzemiennych wśród społeczności grupy kościańskiej kultury unietyckiej – analiza typologiczno-chronologiczna materiałów z Niziny Wielkopolsko-Kujawskiej oraz studium przypadku znaleziska z Bronikowa (gm. Śmigiel) - Teska, Sebastian; Pyżewicz, Katarzyna; Majorek, Piotr (Folia Praehistorica Posnaniensia, 2019)
The article focuses on the matter of significance of flint daggers on the area settled by Early Bronze Age societies connected with Únětice Culture Kościan Group. Analytical part is separated into two sections. The first is a case study of a stray find from Bronikowo (com. Śmigiel) and the second involve typological analysis of flint daggers from western part of Polish Lowlands. Results gathered give an overview of an issue propounded in a title.